TEACHER'S BILINGUAL LANGUAGE USE IN AN EFL CLASSROOM: STUDENTS' PERCEPTION - Azimov, Navruz (ENGLISH JOURNAL, 2020)
Using first language in a second language classroom can be beneficial. This study aims at investigating students' perception about the use of L1 in an EFL classroom setting. The study is framed under case study design in which interview was used as the data collection way. The participants of the study are 10 students from private junior high school in Tajikistan. The results show that the perception of the students is positive. The study suggests that teachers can try different ways of bilingual use in their classrooms based on the purposes the teachers want to achieve.